Analisis Komparatif Bank Syariah dan Bank Konvensional di Indonesia - Rudi Purnomo; Masning Syarifah; Ali Makki Hodri (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2018)
This article discusses a comparative analysis of Islamic banks and conventional banks. This article is the result of a literature review and is qualitative. The collected data is analyzed in a comparative manner between Islamic banks and conventional banks which include: sources of funds, Distribution and Use of Bank Funds, Bank Services, advantages and disadvantages of Islamic banks and conventional banks. About sources of funds, conventional banking sources of funds are: Funds originating from within the bank (internal) and funds originating from outside the bank (external). The source of funds for a Sharia Bank is in its capacity as a mudharib by using funds obtained from customers as Shahib al-Mal, who deposit and invest their funds in the bank through the following accounts: Current Account (pure al-Wadiah savings principle), Savings Account, Account general investment, special investment account. About the Distribution and Use of Funds, in conventional banks the funds that have been collected by banks must then be allocated through the Use of Funds for Assets, Use of Funds for Reserves, Use of Funds for Credit, Use of Funds for Securities, Use of Funds for Participation. Distribution and Use of Funds in Sharia Banks are through financing products with profit sharing principles, sale and purchase principles and leasing and qard hasan. Conventional bank services are Letter of Credit (L / C), Clearing, Bank Guarantee, Collection, Travel Check (travelers check), Remittance, Credit Card (credit card), Safe Deposit Box, Phone Banking, Cash Management , and Money Transfer (Transfer). The services offered at Islamic banks are Rahn, Wakalah, Kafalah Hawalah, Ji'alah, Sharf. Regarding the advantages and disadvantages of conventional banks and Islamic banks, both have their respective advantages and disadvantages.